A scavenger peptide prevents methylglyoxal induced pain in mice - Brings, Sebastian; Fleming, Thomas; Beijer, Barbro; Lindner, Thomas; Wischnjow, Artjom; Kender, Zoltán; Peters, Verena; Kopf, Stefan; Haberkorn, Uwe; Mier, Walter; Nawroth, Peter Paul (Biochimica et biophysica acta. Molecular basis of disease, 2017)
The reactive metabolite methylglyoxal (MG) has been identified as mediator of pain. Scavenging of free MG and the prevention of MG-derived post-translational modifications may provide a useful therapeutic treatment. An arginine-rich, fatty acid coupled, cyclic peptide (CycK(Myr)R4E) with high proteolytic stability and prolonged circulation was developed for the scavenging of MG. It was shown to reduce the formation of albumin-MG adducts in vitro and prevented MG-induced pain by reducing plasma MG levels through the formation of peptide-MG adducts in vivo. CycK(Myr)R4E therefore presents a promising option for the treatment of pain and other diabetic complications associated with high MG levels.